2020
DOI: 10.1161/circep.120.008838
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-Free Arrhythmia Ablation Using Scanned Proton Beams

Abstract: Background - Proton beam therapy offers radiophysical properties that are appealing for noninvasive arrhythmia elimination. This study was conducted to use scanned proton beams for ablation of cardiac tissue, investigate electrophysiologic outcomes, and characterize the process of lesion formation in a porcine model using particle therapy. Methods - Twenty-five animals received scanned proton beam irradiation. ECG-gated CT scans were acquired at end-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…Anticipated STAR effects may be explained by a preclinical study by Zhang et al ( 16) that showed how radiotherapy also induces myocardial electrical conduction reprogramming through increased expression of sodium channels (Nav1.5), upregulation of Connexin 43 (involved in gap junction coupling) and Notch signaling activation. Their findings also elucidate a possible reason behind STAR's effectiveness on transmural scars despite the fact that the standard 25 Gy radiation dose doesn't create transmural myocardial lesions in animal models (17).…”
Section: Discussionmentioning
confidence: 88%
“…Anticipated STAR effects may be explained by a preclinical study by Zhang et al ( 16) that showed how radiotherapy also induces myocardial electrical conduction reprogramming through increased expression of sodium channels (Nav1.5), upregulation of Connexin 43 (involved in gap junction coupling) and Notch signaling activation. Their findings also elucidate a possible reason behind STAR's effectiveness on transmural scars despite the fact that the standard 25 Gy radiation dose doesn't create transmural myocardial lesions in animal models (17).…”
Section: Discussionmentioning
confidence: 88%
“…In the previous largest animal study of RSPV isolation using SABR, mild functional echocardiographic abnormalities were reported in some animals during echocardiographic evaluations at 3–6 months, despite no structural abnormalities at the histopathological examination performed immediately after 14 . Additionally, six cases of sudden death after 40 Gy proton-therapy in multiple left ventricular sites among eight pigs associated with a significant left ventricular ejection fraction depression were reported by Hohman et al 25 . The issue of the safety of surrounding organs, including untargeted cardiac tissue, should be considered before applying this technique for human AF treatments.…”
Section: Discussionmentioning
confidence: 92%
“…The overall reduction of LV function without apparent pathological structural changes was also reported by Zei et al 14 . The study by Hohman et al 25 reported cases of sudden death and a clear dose response relationship with the LV dose. In the in vivo study by Bode et al, collateral damage to the AV node that resulted in an AV block after 40 Gy irradiation to RSPV was observed 26 .…”
Section: Discussionmentioning
confidence: 98%
“…Preclinical studies that created structural ablative lesions in the heart utilised doses in the range of 30e55 Gy to create moderate to severe, but not necessarily fullthickness, fibrosis in the atrioventricular node [37,68e70], pulmonary veins [35e37,40] and ventricles [37,70,71] over a 6e24-month period. Independent of location, doses in excess of 40 Gy were effective at producing fibrotic, nonconducting lesions after 6 months [35e37, 70,71]. Of note, these reported dose ranges are higher than the 25 Gy dose described clinically (Figure 2) and the timing of this fibrosis [60] occurs later than the observed clinical benefit [19,20,23e26].…”
Section: Effects On Fibrosismentioning
confidence: 99%
“…Excessive ROS production after radiation therapy can alter mitochondrial membrane stability, create local redox imbalances and cause substantial mitochondrial dysfunction or genomic instability. Although long-term mitochondrial dysfunction may lead to cytochrome c release and induction of apoptosis [85,93,94], as evidenced by the detection of caspase-3 in porcine ventricles treated with >30 Gy after 12e16 weeks [70], short-term dysfunction may cause an acute conduction block in highly metabolic cardiomyocytes. These potential mechanisms may be consistent with several of the phenotypic changes described to date, and the progression from these subacute observations to collagen deposition and scar formation is still under investigation [70].…”
Section: Effects On Functional Conduction Blockmentioning
confidence: 99%